Brain-Inspired Computing International Workshop, BrainComp 2013, Cetraro, Italy, July 8-11, 2013, Revised Selected Papers - Grandinetti, Lucio; Lippert, Thomas; Petkov, Nicolai; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the thoroughly refereed conference proceedings of the International Workshop on Brain-inspired Computing, BrainComp 2013, held in Cetraro, Italy, in July 2013. The 16 revised full papers were carefully reviewed and selected from numerous submissions and cover topics such as brain structure and function as a neuroscience perspective, computational models and brain-inspired computing, HPC and visualization for human brain simulations.
Brain Structure and Function - A Neuroscience Perspective -- Computational Models and Brain-inspired Computing -- HPC and Visualization for Human Brain Simulations.
Keywords: Computer science; Computers; Artificial intelligence; Computer simulation; Image processing; Computer Science; Computation by Abstract Devices; Artificial Intelligence (incl. Robotics).; Simulation and Modeling; Image Processing and Computer Vision; Electronic books